A Dewetted‐Dealloyed Nanoporous Pt Co‐Catalyst Formed on TiO2 Nanotube Arrays Leads to Strongly Enhanced Photocatalytic H2 Production. Issue 2 (7th January 2020) - Ji, Lei; Spanu, Davide; Denisov, Nikita; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco
Abstract: Pt nanoparticles are typically decorated as co‐catalyst on semiconductors to enhance the photocatalytic performance. Due to the low abundance and high cost of Pt, reaching a high activity with minimized co‐catalyst loadings is a key challenge in the field. We explore a dewetting‐dealloying strategy to fabricate on TiO2 nanotubes nanoporous Pt nanoparticles, aiming at improving the co‐catalyst mass activity for H2 generation. For this, we sputter first Pt‐Ni bi‐layers of controllable thickness (nm range) on highly ordered TiO2 nanotube arrays, and then induce dewetting‐alloying of the Pt‐Ni bi‐layers by a suitable annealing step in a reducing atmosphere: the thermal treatment causes the Pt and Ni films to agglomerate and at the same time mix with each other, forming on the TiO2 nanotube surface metal islands of a mixed PtNi composition. In a subsequent step we perform chemical dealloying of Ni that is selectively etched out from the bimetallic dewetted islands, leaving behind nanoporous Pt decorations. Under optimized conditions, the nanoporous Pt‐decorated TiO2 structures show a>6 times higher photocatalytic H2 generation activity compared to structures modified with a comparable loading of dewetted, non‐porous Pt. We ascribe this beneficial effect to the nanoporous nature of the dealloyed Pt co‐catalyst, which provides an increased surface‐to‐volume ratio and thus a more efficient electron transfer and a higher density of active sites at the co‐catalyst surface for H2 evolution. Abstract : Combined dewetting‐alloying and dealloying of metal thin films provides reliable nanostructuring tools to form on TiO2 nanotubes a nanoporous Pt co‐catalyst that exhibits a significantly enhanced mass activity for photocatalytic H2 evolution.